(untitled) (Research, Society and Development, 2022)
Objective: To describe the factors related to the perception of the LGBTQ+ community to professional care in the area of public health. Method: Qualitative research with 10 participants from the LGBTQ+ community, through semi-structured interviews, which were transcribed and analyzed through the methodological framework proposed by Creswell based on the six steps of his proposal; in the theoretical framework the theory of Roy’s adaptation and the basis for gender issues, using Judith Buttler as a reference. Results: After the analysis of the interviews, four categories of analysis emerged: 1. The difference in the professional look during the service; 2. Sexual orientation and gender identity as causes of suffering; 3. The birth body and the wrong body sensation; 4. Gender equality as a necessity for professional care. With the definition of the classes it was possible to construct a grammar structure according to Roy’s adaptation model. Conclusion: Evidenced that Callista Roy’s theory of adaptation, it underpits a humanized care and care focused on the integrality of the individual and, therefore, that can be used with the LGBTQ+ community.